Application of supercritical fluid extraction (SFE) of palm oil and oil from natural sources - Akanda, Md. Jahurul Haque; Sarker, Md. Zaidul Islam; Ferdosh, Sahena; Abdul Manap, Mohd Yazid; Nik Abdul Rahman, Nik Norulaini; Abd Kadir, Mohd Omar (MDPI, 2012)
Supercritical fluid extraction (SFE) has received much interest in the use and further development for industrial application, a method which offers some advantages over the conventional methods, especially for the palm oil industry. Supercritical fluid extraction (SFE) uses carbon dioxide (CO2) as a solvent, denoted as SC-CO2 which is nontoxic, inexpensive, nonflammable, and nonpolluting supercritical fluid solvent for the extraction of natural products. Almost 100% oil can be extracted and is regarded as safe, organic solvent-free extracts having superior organoleptic profile. Palm oil industry is one of the major industries in Malaysia that provides principal contribution to the national income. Malaysia is the second largest palm oil and palm kernel oil producer around the world. The aim of this paper reviews advance applications of supercritical carbon dioxide (SC-CO2) extraction of oils from natural sources in particular, palm oil, minor constituents in palm oil, producing fractionated, refined, bleached, and deodorized palm oil, palm kernel oil and purified fatty acid fractions commendable for downstream uses as in toiletries and confectionaries.